A systematic scoping review of interventions to integrate physical and mental healthcare for people with serious mental illness and substance use disorders. (September 2020) - Richardson, Amy; Richard, Lauralie; Gunter, Kathryn; Cunningham, Ruth; Hamer, Helen; Lockett, Helen; Wyeth, Emma; Stokes, Tim; Burke, Martin; Green, Mel; Cox, Adell; Derrett, Sarah
Abstract: Integrated care approaches have been recommended to remove barriers to healthcare and improve the physical health outcomes of people living with serious mental illness (SMI) and/or substance use disorders (SUDs). The aim of this systematic scoping review was to describe empirical investigations of interventions designed to integrate physical, mental, and addiction healthcare for this population. An iterative and systematic search of five electronic databases (Medline (Ovid), PsycINFO, CINAHL, Embase (Ovid) and Scopus) was conducted to identify peer-reviewed articles published between January 2000 and April 2019. Two reviewers independently screened publications in two successive stages of title and abstract screening, followed by full-text screening of eligible publications. Data from each included publication were extracted independently by two reviewers using a standardised spreadsheet. A total of 28 eligible publications were identified, representing 25 unique studies. Over half of the included studies investigated the use of case managers to provide self-management skills or to coordinate mental and physical healthcare (n = 14). Other interventions examined the co-location of services (n = 9) and the implementation of screening and referral pathways to specialist treatment (n = 2). Less than half of the included studies described a framework, theory or model that was underpinning the intervention tested. While some aspects of integrated care have been identified and addressed by interventions, other key dimensions have not been considered, such as shared decision-making. Identification of a comprehensive model of integrated care is recommended to inform the development and evaluation of future interventions for people with SMI/SUDs.